1973
DOI: 10.1037/h0035531
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of extinction gradients: A systematic analysis.

Abstract: In Experiment I, rats \vcrc trained to press a bar to obtain food in the presence of a tone. A gradient of stimulus generalization was obtained by testing groups of .S' s to stimuli varying along a tonal dimension, with each 5 being tested at only one stimulus until it reached an extinction criterion. Following this phase, all 5s were shifted back to the original training tone, and the extinction procedure was continued. This second shift yielded a gradient of generalization of extinction. Experiment II held c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…Supporting this prediction, some prior studies have yielded evidence for generalization of extinction across CSs (Pavlov, 1927; Dubin and Levis, 1974). However, other studies have reported that responding diminishes selectively to the extinguished CS and not other CSs (Bouton and King, 1983; Holland and Lamare, 1984; Richards and Sargent, 1984).…”
Section: Discussionmentioning
confidence: 79%
“…Supporting this prediction, some prior studies have yielded evidence for generalization of extinction across CSs (Pavlov, 1927; Dubin and Levis, 1974). However, other studies have reported that responding diminishes selectively to the extinguished CS and not other CSs (Bouton and King, 1983; Holland and Lamare, 1984; Richards and Sargent, 1984).…”
Section: Discussionmentioning
confidence: 79%
“…The use of a different duration CS+ during extinction would result in a generalization gradient at extinction re-test: the less similar the extinction CS+ duration was to the acquisition CS+ duration, the less effective extinction will be at reducing responding at re-test (extinction re-test generalization decrement: attenuated reduction in responding due to generalization). Such generalization gradients for extinction performance and re-test have been shown in appetitive paradigms using auditory tones of different frequencies (as opposed to different durations) (e.g., Dubin & Levis, 1973). A similar pattern has also been observed in human fear conditioning using geometric shapes as CSs (Vervliet, Vansteenwegen, & Eelen, 2004).…”
mentioning
confidence: 61%
“…Subjects extinguished on cues shorter than the training duration never experience the full training duration in extinction. Dubin and Levis (1973) reported a similar, but more symmetric, transfer pattern when the similarity of the training and extinction cue was varied in another way. In their study the frequency of a tone CS was varied between training and extinction.…”
Section: Discussionmentioning
confidence: 82%
“…Changes in other features of the CS have a similar effect. The design of the current experiments is very similar to that of Dubin and Levis (1973), who studied the effect of varying the frequency of a tone CS between training and extinction. They found that such changes reduced the amount of responding during the extinction treatment.…”
Section: Discussionmentioning
confidence: 99%